Sustainability of using vineyard pruning residues as an energy source: Combustion performances and environmental impact. (1st May 2019) - Giorio, Chiara; Pizzini, Sarah; Marchiori, Enrico; Piazza, Rossano; Grigolato, Stefano; Zanetti, Michela; Cavalli, Raffaele; Simoncin, Marco; Soldà, Lidia; Badocco, Denis; Tapparo, Andrea
Graphical abstract: Highlights: Assessment of the sustainability of using vineyard pruning residues for energy conversion. Characterization of the physico-mechanical properties of the wood chips. Quantification of the primary emissions of CO2, CO, NOx, SO2 and particulate matter. Quantification of the primary emissions, and related toxic potential, of PCDD/Fs, PCBs and PAHs. Characterization of combustion ashes in view of their possible reutilization as soil amendments. Abstract: Open burning of agricultural waste is still a common practice as it is a rapid method for waste disposal, although natural biomass, including agriculture residues, can be exploited as a renewable energy source. We assessed the viability and sustainability of using vineyard pruning residues, as wood chips, for energy conversion. Wood chips, obtained from vineyards in the Prosecco DOCG region (Italy), were characterized in terms of chemical composition, calorific value, ash content and humidity. Combustion tests were performed in a medium-size biomass boiler (maximum power 500 kW) to assess the viability of the approach in terms of sustainable steady-state combustion. Primary emissions of both macro- and micro-pollutants were measured to assess the environmental impact. An analytical method was purposely developed for the determination of polycyclic aromatic hydrocarbons (PAHs), polychlorinated biphenyls (PCBs), polychlorinated dibenzo-p-dioxins (PCDDs) and polychlorinated dibenzofurans (PCDFs) in three matrices: fly ashes, condensate and gas. The results showed that vineyard pruning residues can be used for energy conversion in medium- and large-scale biomass boilers. Primary emissions of measured pollutants were all below limit values set by current European legislation except for particulate matter, for which current available abatement technologies are required to contain emissions, thus making the use of vineyard pruning residues unsuitable for combustion in domestic appliances where such technologies are not installed. Bottom ashes produced during combustion were also characterized to assess whether they can be recycled in the vineyard as soil amendments/fertilizers. Copper content in combustion ashes exceeded limit values for ashes to be used as fertilizers in agricultural fields for some European countries but not for others, indicating that ashes may need to be disposed as waste.